INSECTICIDE TWINGO EURO, MD S.K. IN THE FIGHT AGAINST LEAF ROLLERS AND SCALE INSECTS ON THE APPLE TREE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The insecticide Twingo Euro, MD s.k. showed high efficacy against leaf rollers and scale insects on apple trees at a rate of 0.5-0.8 l/ha. We recommend the insecticide Twingo Euro, MD s.k. for use against leaf rollers and scale insects on apple at a rate of 0.5-0.8 l/ha. by treatment during the growing season of the plant.